The effect of acid-base synergistic catalysis on upgrading of volatiles from coal pyrolysis over Mg-Al composite oxides. (1st August 2022) - Yang, Hang; Zhang, Jiehan; Li, Changming; Chen, Zhaohui; Wang, Demin; Wang, Deliang; Ibrahim Sharif, Munnir; Li, Jianling; Yu, Jian; Gao, Shiqiu
Highlights: Mg x Al-LDOs with tunable acid-base property were prepared for pyrolysis volatiles upgrading. The quality of tar and gas was improved over Mg x Al-LDOs with less carbon deposition. The content of light aromatic hydrocarbons increased by 79.8% over Mg4 Al-LDO catalyst. The acid-base synergistic effect of Mg x Al-LDOs plays the key role in the upgrading of volatiles. Abstract: Catalytic upgrading of coal pyrolysis volatiles is one of the most promising technical routes to achieve graded utilization of low-rank coal resource. In this work, a series of Mg-Al composite oxide catalysts (Mg x Al-LDOs) were synthesized with tunable acid-base properties for upgrading the volatiles from coal pyrolysis by adjusting the Mg/Al ratio in Mg-Al hydrotalcite precursors (Mg x Al-LDHs). The NH3 -TPD and CO2 -TPD analysis results showed the quantity of acidity sites decrease together with an increase of basicity sites as the Mg/Al ratio increased in Mg x Al-LDOs. Mg x Al-LDOs possessed weaker acidity strength and more acidity sites than pure Al2 O3, but less basicity sites than pure MgO. The catalytic performances illustrated that the increased acidity sites in Mg x Al-LDOs promoted the cracking of heavy components and reduced the yield of heavy tar. Meanwhile, the weakened acidity strength and the introduction of basicity sites by Mg in Mg x Al-LDOs enhanced the strong resistance to carbon deposition. Moreover, the CO2 yield and the content of light aromatic hydrocarbons in tar increased obviously after upgrading, which can be attributed to the acid-base synergistic effect of the Mg x Al-LDOs. Particularly, the Mg4 Al-LDO catalyst selectively improved the relative contents of light aromatic hydrocarbons, and the content of benzene, toluene, ethylbenzene, xylene, naphthalene and indene increased by 1.48, 1.54, 0.76, 2.56, 0.19 and 2.14 times (compared with the inert quartz sand), respectively. The unique catalytic behaviors of Mg x Al-LDO catalysts will provide a new insight into the effect of acid-base synergistic catalysis on upgrading of volatiles from coal pyrolysis.